Optimizing ICT Infrastructure for Enhanced Agricultural Productivity in Lampung Province, Indonesia: Challenges and Opportunities - Muhida, Riza (Journal of Applied Science and Advanced Engineering, 2025)
Lampung Province, one of Indonesia's key agrarian regions, plays a critical role in national food security. However, the agricultural sector faces significant challenges, including low productivity, resource inefficiency, and the adverse effects of climate change. The integration of Information and Communication Technology (ICT), such as the Internet of Things (IoT), precision agriculture, and big data analytics, offers innovative solutions to these challenges. This paper explores the potential of ICT to enhance agricultural productivity in Lampung Province by analyzing case studies from Indonesia and globally. The study identifies key challenges, including limited internet infrastructure, low digital literacy among farmers, high technology costs, and insufficient technical support. Strategic recommendations are proposed, such as strengthening ICT infrastructure in rural areas, providing subsidies and incentives for farmers, increasing digital literacy through training programs, and developing IoT-based pilot projects. The findings highlight the importance of ICT in modernizing agriculture, improving farmers' welfare, and ensuring sustainable development. By addressing these challenges and leveraging ICT, Lampung Province can transform its agricultural sector, contributing to both regional and national food security